Method for forming Cf / SiC ceramic composite material through FDM technology

Through the FDM technology, the method of forming Cf/SiC ceramic composites has been solved, and the problem of low surface accuracy of FDM printing parts has been achieved, efficient and low-cost ceramic composite materials are achieved, and the material performance is enhanced. It is suitable for the production of personalized and special-shaped parts. .

CN119191861APending Publication Date: 2024-12-27IANGSU COLLEGE OF ENG & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393071.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The method of preparing Cf/SiC ceramic composites in FDM type 3D printing has a step effect, and the surface accuracy of the ceramic matrix composites cannot be guaranteed, limiting its application in the preparation of personalized products and special-shaped parts.

Method used

The method of forming Cf/SiC ceramic composite materials using FDM technology includes steps such as establishing a three-dimensional model, setting FDM printer parameters, degreasing, impregnation, cross-linking curing and cracking, and processing them in an inert atmosphere through a vacuum sintering furnace to form a pyrolytic carbon layer. To enhance material properties.

Benefits of technology

It effectively overcomes the step effect, improves the surface accuracy of parts, reduces production costs, realizes efficient preparation of personalized products and special-shaped parts, and enhances the performance of Cf/SiC composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191861A_ABST
    Figure CN119191861A_ABST
Patent Text Reader

Abstract

The invention discloses a method for forming a Cf / SiC ceramic composite material through an FDM technology, and belongs to the field of 3D printing ceramic matrix composite materials. The method aims at solving the problems that an obvious step effect exists in an existing method for preparing the Cf / SiC ceramic composite material through FDM type 3D printing, and the surface precision of the ceramic-based composite material cannot be guaranteed. The method comprises the following steps: 1, establishing a three-dimensional model; 2, setting parameters of an FDM printer and printing a primary blank; 3, degreasing; 4, dipping; 5, cross-linking and curing; 6, cracking; and 7, repeatedly dipping, cross-linking curing and cracking. The method is used for forming the Cf / SiC ceramic composite material through the FDM technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of 3D printing ceramic-based composite materials. Background Art

[0002] Silicon carbide ceramics have excellent properties such as low density, high strength, and high temperature resistance. They are widely used in aerospace, energy, petrochemical and other fields. However, due to its inherent properties, it has disadvantages such as high brittleness and low tensile strength, which results in poor machinability and hinders the development and application of silicon carbide ceramic materials. The composite of carbon fiber and silicon carbide to form silicon carbide-based ceramic composites is known as an effective means to improve the high brittleness and low tensile strength of silicon carbide. The choice of composite method is favored by many researchers. Traditional composite methods are mostly achieved by three-dimensional weaving, which requires the use of molds to form the corresponding shape, and have the disadvantages of complex process, high cost, and long production cycle. To a certain extent, it limits the application expansion of silicon carbide-based composite materials, especially in the preparation of small batches of special-shaped parts or personalized customization. It cannot meet the market's demand for technological innovation. With the development of 3D printing technology, some 3D printing equipment can be used with corresponding post-processing processes to realize the preparation of silicon carbide-based ceramic composites, such as SLS combined with PIP process to prepare SiC f / SiC composite materials, etc., have contributed to the development of ceramic-based composite materials. The use of FDM 3D printers with strong universality and low cost to prepare C f The method of additive manufacturing of ceramic matrix composites has obvious step effect, which cannot guarantee the surface accuracy of ceramic matrix composites and limits the application of additive manufacturing of ceramic matrix composites. Summary of the invention

[0003] The present invention aims to solve the existing FDM type 3D printing preparation C f The method of forming C / SiC ceramic composites has obvious step effect and cannot ensure the surface accuracy of ceramic matrix composites. f / SiC ceramic composites.

[0004] A FDM technology molding C f The method for preparing a SiC / SiC ceramic composite material is carried out according to the following steps:

[0005] 1. Build a 3D model:

[0006] Draw 3D models and import them into layered slicing software;

[0007] 2. Set FDM printer parameters and print the first blank:

[0008] The FDM printer parameters were set to 0.20 mm to 0.6 mm layer height, 200 °C to 500 °C printing temperature, 60% to 100% filling density, 0.4 mm to 0.8 mm wall thickness, 10% to 30% filling overlap, 50% to 100% nozzle movement speed, 10 mm / s to 40 mm / s nozzle retraction speed, and 4 mm to 8 mm nozzle retraction length. f The matrix of the wire is FDM printed, and after printing, wait for 10 to 30 minutes, then take out the print, and obtain the C f The initial blank;

[0009] 3. Degreasing:

[0010] Contains C f The blank is placed in a vacuum sintering furnace, first heated to 1000℃~1200℃ in N2 atmosphere, then degreased for 20min~40min in N2 atmosphere and temperature of 1000℃~1200℃, and finally cooled in N2 atmosphere to obtain C f skeleton;

[0011] 4. Impregnation:

[0012] C f The skeleton is immersed in the precursor solution and vacuumized and pressurized to obtain a C containing the precursor solution. f skeleton;

[0013] The precursor solution is composed of polycarbosilane, divinylbenzene and tetrahydrofuran;

[0014] 5. Cross-linking and curing:

[0015] The C containing precursor solution f The skeleton is heated to 300°C to 320°C, cross-linked and cured for 5h to 10h at a temperature of 300°C to 320°C, and then cooled to obtain a cross-linked and cured C-containing f Frame material;

[0016] 6. Cracking:

[0017] After cross-linking and curing, the C f The skeleton material is placed in a vacuum sintering furnace, first heated to 1100℃~1300℃ in N2 atmosphere, then cracked for 20min~40min in N2 atmosphere and temperature of 1100℃~1300℃, and finally cooled in N2 atmosphere to obtain a C-containing primary cracking product. f Frame material;

[0018] 7. Repeated impregnation, cross-linking, curing and cracking:

[0019] The C fRepeat steps 4 to 6 until the skeleton material is dense, and obtain C f / SiC ceramic composite materials.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention can overcome the step effect of FDM molded parts and effectively ensure the surface accuracy of the parts;

[0022] 2. The present invention uses the FDM technology with high universality and low cost to form C f / SiC composite material, which has the characteristics of easy operation and simple process;

[0023] 3. The present invention adopts FDM molding to contain C f Preliminary blanks can significantly reduce production costs and have unparalleled advantages in realizing personalized products or special-shaped parts preparation;

[0024] Fourth, the degreasing process of the present invention is to sinter the polymer material in an inert gas environment to obtain a certain amount of pyrolytic carbon coated on C f The surface of the pyrolytic carbon layer is formed, which can form a good interface with the SiC obtained by subsequent polycarbosilane cracking, which is beneficial to the strengthening of C f The performance of / SiC composites is of great significance.

[0025] Instruction Manual

[0026] Figure 1 The C-containing f Appearance diagram of the initial blank;

[0027] Figure 2 C prepared in Example 1 f / Appearance of SiC ceramic composite material;

[0028] Figure 3 The C-containing pyrolysis product prepared in step 6 of Example 1 f Cross-sectional morphology of the skeleton material;

[0029] Figure 4 The C-containing pyrolysis product prepared in step 6 of Example 1 f A magnified image of the cross-sectional morphology of the skeleton material;

[0030] Figure 5 In step 7 of Example 1, the C-containing f The morphology of the skeleton material after steps 4 to 6 were repeated 3 times;

[0031] Figure 6 In step 7 of Example 1, the C-containing f The morphology of the skeleton material after steps 4 to 6 were repeated 8 times. DETAILED DESCRIPTION

[0032] Specific implementation method 1: This implementation method is a FDM technology forming C f The method for preparing a SiC / SiC ceramic composite material is carried out according to the following steps:

[0033] 1. Build a 3D model:

[0034] Draw 3D models and import them into layered slicing software;

[0035] 2. Set FDM printer parameters and print the first blank:

[0036] The FDM printer parameters were set to 0.20 mm to 0.6 mm layer height, 200 °C to 500 °C printing temperature, 60% to 100% filling density, 0.4 mm to 0.8 mm wall thickness, 10% to 30% filling overlap, 50% to 100% nozzle movement speed, 10 mm / s to 40 mm / s nozzle retraction speed, and 4 mm to 8 mm nozzle retraction length. f The matrix of the wire is FDM printed, and after printing, wait for 10 to 30 minutes, then take out the print, and obtain the C f The initial blank;

[0037] 3. Degreasing:

[0038] Contains C f The blank is placed in a vacuum sintering furnace, first heated to 1000℃~1200℃ in N2 atmosphere, then degreased for 20min~40min in N2 atmosphere and temperature of 1000℃~1200℃, and finally cooled in N2 atmosphere to obtain C f skeleton;

[0039] 4. Impregnation:

[0040] C f The skeleton is immersed in the precursor solution and vacuumized and pressurized to obtain a C containing the precursor solution. f skeleton;

[0041] The precursor solution is composed of polycarbosilane, divinylbenzene and tetrahydrofuran;

[0042] 5. Cross-linking and curing:

[0043] The C containing precursor solution f The skeleton is heated to 300°C to 320°C, cross-linked and cured for 5h to 10h at a temperature of 300°C to 320°C, and then cooled to obtain a cross-linked and cured C-containing f Frame material;

[0044] 6. Cracking:

[0045] After cross-linking and curing, the C f The skeleton material is placed in a vacuum sintering furnace, first heated to 1100℃~1300℃ in N2 atmosphere, then cracked for 20min~40min in N2 atmosphere and temperature of 1100℃~1300℃, and finally cooled in N2 atmosphere to obtain a C-containing primary cracking product. f Frame material;

[0046] 7. Repeated impregnation, cross-linking, curing and cracking:

[0047] The C f Repeat steps 4 to 6 until the skeleton material is dense, and obtain C f / SiC ceramic composite materials.

[0048] In step 1 of this specific implementation method, a three-dimensional model is drawn using three-dimensional modeling software and exported to .STL format, which is then imported into layered slicing software.

[0049] In step 2 of this specific implementation method, before printing, the four leveling bolts of the printing platform need to be adjusted and the printer nozzle needs to be moved so that the distance between the nozzle and the workbench is equal, thus completing the leveling of the workbench;

[0050] The parameter setting described in step 2 of this specific implementation method also includes bottom support and support structure; the bottom support is mainly to prevent the first layer of the blank from warping or loose bonding with the workbench, and the support structure includes a zigzag structure, a straight line structure and a linear structure, and its main function is to support the printing and forming of parts and prevent empty printing.

[0051] In this specific implementation method, the parameters set in step 2 directly start the FDM printer to print or save the parameters as a .Gcode file in a USB flash drive. Insert the USB flash drive into the FDM port and wait for the file to be recognized. The printer is preheated and the water cooling device is started. When the preset temperature is reached, printing begins. After printing is completed, wait for 10 to 30 minutes, open the FDM printing safety door, and take out the C f Initial blank, remove unnecessary supports.

[0052] The beneficial effects of this embodiment are:

[0053] 1. This implementation method can overcome the step effect of FDM molded parts and effectively ensure the surface accuracy of the parts;

[0054] Second, this implementation method uses the FDM technology with high universality and low cost to form C f / SiC composite material, which has the characteristics of easy operation and simple process;

[0055] 3. This embodiment adopts FDM molding containing C f Preliminary blanks can significantly reduce production costs and have unparalleled advantages in realizing personalized products or special-shaped parts preparation;

[0056] Fourth, the degreasing process of this embodiment is to sinter the polymer material in an inert gas environment to obtain a certain amount of pyrolytic carbon coated on C f The surface of the pyrolytic carbon layer is formed, which can form a good interface with the SiC obtained by subsequent polycarbosilane cracking, which is beneficial to the strengthening of C f The performance of / SiC composites is of great significance.

[0057] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: the C-containing f The matrix of the wire is C-containing f Thermoplastic material of the wire: the thermoplastic material is PLA, PA or ABS. Others are the same as the first embodiment.

[0058] Specific implementation method three: This implementation method is different from either specific implementation method one or two in that: the C-containing f C in the matrix of the wire f The mass percentage of the wire material is 5% to 10%. The rest is the same as the first or second specific implementation.

[0059] Specific implementation method 4: This implementation method is different from the specific implementation methods 1 to 3 in that: the C f The diameter of the wire is 1.6 mm to 1.8 mm. Other aspects are the same as those of the first to third embodiments.

[0060] Specific implementation mode 5: This implementation mode is different from the specific implementation modes 1 to 4 in that: the heating to 1000℃~1200℃ in N2 atmosphere described in step 3 is specifically carried out according to the following steps: heating to 100℃~150℃ at a heating rate of 3℃ / min~8℃ / min, and then heating to 1000℃~1200℃ at a heating rate of 5℃ / min~10℃ / min; cooling in N2 atmosphere described in step 3 is specifically carried out according to the following steps: cooling to 150℃~200℃ at a cooling rate of 5℃ / min~10℃ / min, and then cooling to 80℃~100℃ at a cooling rate of 3℃ / min~8℃ / min, and finally cooling to room temperature with furnace water. Others are the same as specific implementation modes 1 to 4.

[0061] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the vacuuming and pressurizing described in step 4 are performed by using a vacuum pressure impregnation machine, under the condition of -0.1MPa to 0MPa, vacuuming for 30min to 60min, and then pressurizing for 30min to 60min under the condition of 1MPa to 3MPa, and then taking out after exhausting. The rest is the same as specific embodiments 1 to 5.

[0062] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the precursor solution described in step 4 is specifically prepared by stirring polycarbosilane, divinylbenzene and tetrahydrofuran at a temperature of 30°C to 50°C until the polycarbosilane is dissolved; the mass ratio of the polycarbosilane to the tetrahydrofuran is (1 to 1.5):1; the mass ratio of the divinylbenzene to the tetrahydrofuran is (3 to 5):1. The rest is the same as specific embodiments 1 to 6.

[0063] Specific embodiment eight: This embodiment is different from specific embodiments one to seven in that: the heating to 300℃~320℃ described in step five is specifically carried out according to the following steps: heating to 80℃~100℃ at a heating rate of 3℃ / min~5℃ / min, then heating to 200℃~220℃ at a heating rate of 5℃ / min~10℃ / min, and then heating to 300℃~320℃ at a heating rate of 3℃ / min~8℃ / min; the cooling described in step five is specifically carried out according to the following steps: cooling to 200℃~220℃ at a cooling rate of 3℃ / min~8℃ / min, then cooling to 80℃~100℃ at a cooling rate of 5℃ / min~10℃ / min, and then cooling to room temperature at a cooling rate of 3℃ / min~5℃ / min. The rest is the same as specific embodiments one to seven.

[0064] Specific implementation method 9: This implementation method is different from specific implementation methods 1 to 8 in that: the heating to 1100℃~1300℃ in N2 atmosphere described in step 6 is specifically carried out according to the following steps: heating to 80℃~100℃ at a heating rate of 3℃ / min~8℃ / min, then heating to 700℃~800℃ at a heating rate of 5℃ / min~10℃ / min, and then heating to 1100℃~1300℃ at a heating rate of 3℃ / min~8℃ / min; cooling in N2 atmosphere described in step 6 is specifically carried out according to the following steps: cooling to 700℃~800℃ at a cooling rate of 3℃ / min~8℃ / min, then cooling to 80℃~100℃ at a cooling rate of 5℃ / min~10℃ / min, and finally cooling to room temperature with furnace water. Others are the same as specific implementation methods 1 to 8.

[0065] Specific embodiment 10: This embodiment differs from the first to ninth embodiments in that: in step 7, the C-containing f The skeleton material is prepared by repeating steps 4 to 6 until the weight gain is ≤ 1%. The rest is the same as the specific embodiments 1 to 9.

[0066] The following examples are used to verify the beneficial effects of the present invention:

[0067] Embodiment 1:

[0068] A FDM technology molding C f The method for preparing a SiC / SiC ceramic composite material is carried out according to the following steps:

[0069] 1. Build a 3D model:

[0070] Draw 3D models and import them into layered slicing software;

[0071] 2. Set FDM printer parameters and print the first blank:

[0072] The FDM printer parameters were set to 0.4 mm layer height, 300 °C printing temperature, 100% filling density, 0.4 mm wall thickness, 20% filling overlap, 80% nozzle moving speed, 20 mm / s nozzle retraction speed, and 6 mm nozzle retraction length. f The matrix of the wire is FDM printed, and after printing, wait for 20 minutes, then take out the print, and obtain the C f The initial blank;

[0073] 3. Degreasing:

[0074] Contains C f The blank was placed in a vacuum sintering furnace, first heated to 1000°C in a N2 atmosphere, then degreased for 40 min in a N2 atmosphere at 1000°C, and finally cooled in a N2 atmosphere to obtain C f skeleton;

[0075] 4. Impregnation:

[0076] C f The skeleton was immersed in the precursor solution, and a vacuum pressure impregnation machine was used to evacuate the solution at a pressure of -0.1 MPa for 50 min, and then pressurized at a pressure of 3 MPa for 50 min. The skeleton was then taken out after exhausting the pressure to obtain a C-containing precursor solution. f skeleton;

[0077] The precursor solution is composed of polycarbosilane, divinylbenzene and tetrahydrofuran;

[0078] 5. Cross-linking and curing:

[0079] The C containing precursor solution f The skeleton was heated to 320°C, cross-linked and cured for 6 hours at 320°C, and then cooled to obtain a cross-linked and cured C-containing f Frame material;

[0080] 6. Cracking:

[0081] After cross-linking and curing, the C f The skeleton material was placed in a vacuum sintering furnace, first heated to 1200°C in a N2 atmosphere, then degreased for 30 min in a N2 atmosphere at 1200°C, and finally cooled in a N2 atmosphere to obtain a C-containing primary cracking f Frame material;

[0082] 7. Repeated impregnation, cross-linking, curing and cracking:

[0083] The C f The skeleton material is repeated nine times according to steps 4 to 6, and the weight gain rate is ≤ 1% to reach a dense state, and C f / SiC ceramic composite material, the standard sample size is 36mm×4mm×3mm.

[0084] The C-containing f The matrix of the wire is provided by Nanjing Special Plastic Composite Materials Co., Ltd. f The thermoplastic material of the wire is specifically a PA-based short fiber reinforced material.

[0085] The C-containing f C in the matrix of the wire f The mass percentage of the wire is 5%; the C f The diameter of the wire is 1.75 mm.

[0086] The heating to 1000°C in N2 atmosphere described in step three is specifically carried out according to the following steps: heating to 150°C at a heating rate of 3°C / min, and then heating to 1000°C at a heating rate of 5°C / min; cooling in N2 atmosphere described in step three is specifically carried out according to the following steps: cooling to 150°C at a cooling rate of 5°C / min, and then cooling to 100°C at a cooling rate of 3°C / min, and finally cooling to room temperature with furnace water.

[0087] The precursor solution described in step 4 is specifically prepared by stirring polycarbosilane, divinylbenzene and tetrahydrofuran at a temperature of 50° C. until the polycarbosilane is dissolved; the mass ratio of the polycarbosilane to tetrahydrofuran is 1.5:1; and the mass ratio of the divinylbenzene to tetrahydrofuran is 4:1.

[0088] The heating to 320°C described in step 5 is specifically carried out according to the following steps: heating to 100°C at a heating rate of 3°C / min, then heating to 220°C at a heating rate of 5°C / min, and then heating to 320°C at a heating rate of 3°C / min; the cooling described in step 5 is specifically carried out according to the following steps: cooling to 220°C at a cooling rate of 3°C / min, then cooling to 100°C at a cooling rate of 5°C / min, and then cooling to room temperature at a cooling rate of 3°C / min.

[0089] The heating to 1200°C in N2 atmosphere described in step six is ​​specifically carried out according to the following steps: heating to 100°C at a heating rate of 3°C / min, then heating to 800°C at a heating rate of 10°C / min, and then heating to 1200°C at a heating rate of 5°C / min; cooling in N2 atmosphere described in step six is ​​specifically carried out according to the following steps: cooling to 800°C at a cooling rate of 5°C / min, then cooling to 100°C at a cooling rate of 10°C / min, and finally cooling to room temperature with furnace water.

[0090] According to GB / T8489-2006 "Test Method for Compression Strength of Fine Ceramics", GB / T6569-2006 "Test Method for Bending Strength of Fine Ceramics" and GB / T23806-2009 "Test Method for Fracture Toughness of Fine Ceramics - Single Edge Precracked Beam (SEPB) Method", the C prepared in Example 1 was tested. f / SiC ceramic composite materials were tested for compressive strength, flexural strength and fracture toughness. Under room temperature, the compressive strength was 167.62MPa, the flexural strength was 143.57MPa, and the fracture toughness was 4.75MPa·m 1 / 2 ; Under 1200℃ vacuum environment, the compressive strength is 159.24MPa, the bending strength is 139.24MPa, and the fracture toughness is 4.63MPa·m 1 / 2 .

[0091] Figure 1 The C-containing f Appearance of the initial blank; As can be seen from the figure, the appearance of the parts prepared by FDM has an obvious step effect, and there are obvious "traces" between layers.

[0092] Figure 2 C prepared in Example 1 f / Appearance of SiC ceramic composite material; as can be seen from the figure, there are no obvious "traces" on the surface of the part.

[0093] Figure 3 The C-containing pyrolysis product prepared in step 6 of Example 1 fCross-sectional morphology of the skeleton material; it can be seen from the figure that after one cycle of immersion and cracking, the sample contains a large number of pores and C fibers.

[0094] Figure 4 The C-containing pyrolysis product prepared in step 6 of Example 1 f A magnified image of the cross-sectional morphology of the skeleton material; as can be seen from the image, the surface of the C fiber is covered with a layer of pyrolytic carbon.

[0095] Figure 5 In step 7 of Example 1, the C-containing f The morphology of the skeleton material after steps 4 to 6 were repeated 3 times; it can be seen from the figure that the C fibers are basically wrapped by the SiC generated by impregnation and pyrolysis, but a certain amount of pores can still be observed inside the matrix.

[0096] Figure 6 In step 7 of Example 1, the C-containing f The morphology of the skeleton material after repeating steps 4 to 6 for 8 times. As can be seen from the figure, the matrix has become dense, the C fibers are completely wrapped by the SiC generated by impregnation and pyrolysis, and macropores are difficult to observe.

Claims

1. A FDM technology molding C f / SiC ceramic composite material method, characterized in that It is carried out in the following steps:

1. Build a 3D model: Draw 3D models and import them into layered slicing software; 2. Set FDM printer parameters and print the first blank: The FDM printer parameters were set to 0.20 mm to 0.6 mm layer height, 200 °C to 500 °C printing temperature, 60% to 100% filling density, 0.4 mm to 0.8 mm wall thickness, 10% to 30% filling overlap, 50% to 100% nozzle movement speed, 10 mm / s to 40 mm / s nozzle retraction speed, and 4 mm to 8 mm nozzle retraction length. f The matrix of the wire is FDM printed, and after printing, wait for 10 to 30 minutes, then take out the print, and obtain the C f The initial blank; 3. Degreasing: Will contain C f The blank is placed in a vacuum sintering furnace, first heated to 1000℃~1200℃ in N2 atmosphere, then degreased for 20min~40min in N2 atmosphere and temperature of 1000℃~1200℃, and finally cooled in N2 atmosphere to obtain C f skeleton; 4. Impregnation: C f The skeleton is immersed in the precursor solution and vacuumized and pressurized to obtain a C containing the precursor solution. f skeleton; The precursor solution is composed of polycarbosilane, divinylbenzene and tetrahydrofuran; 5. Cross-linking and curing: The C containing precursor solution f The skeleton is heated to 300°C to 320°C, cross-linked and cured for 5h to 10h at a temperature of 300°C to 320°C, and then cooled to obtain a cross-linked and cured C-containing f Frame material; 6. Cracking: After cross-linking and curing, the C f The skeleton material is placed in a vacuum sintering furnace, first heated to 1100℃~1300℃ in N2 atmosphere, then cracked for 20min~40min in N2 atmosphere and temperature of 1100℃~1300℃, and finally cooled in N2 atmosphere to obtain a C-containing primary cracking product. f Frame material; 7. Repeated impregnation, cross-linking, curing and cracking: The C f Repeat steps 4 to 6 until the skeleton material is dense, and obtain C f / SiC ceramic composite materials.

2. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that The C-containing f The matrix of the wire is C-containing f Thermoplastic material of the wire; the thermoplastic material is PLA, PA or ABS.

3. The FDM molding method according to claim 2 f / SiC ceramic composite material method, characterized in that The C-containing f C in the matrix of the wire f The mass percentage of the wire is 5% to 10%.

4. The FDM molding method according to claim 3 f / SiC ceramic composite material method, characterized in that The C f The diameter of the wire is 1.6mm to 1.8mm.

5. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that The heating to 1000℃~1200℃ in N2 atmosphere described in step 3 is specifically carried out according to the following steps: heating to 100℃~150℃ at a heating rate of 3℃ / min~8℃ / min, and then heating to 1000℃~1200℃ at a heating rate of 5℃ / min~10℃ / min; cooling in N2 atmosphere described in step 3 is specifically carried out according to the following steps: cooling to 150℃~200℃ at a cooling rate of 5℃ / min~10℃ / min, and then cooling to 80℃~100℃ at a cooling rate of 3℃ / min~8℃ / min, and finally cooling to room temperature with furnace water.

6. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that The vacuuming and pressurizing described in step 4 are specifically performed using a vacuum pressure impregnation machine, under a pressure of -0.1MPa to 0MPa, vacuuming for 30min to 60min, and then pressurizing for 30min to 60min under a pressure of 1MPa to 3MPa, and then taking out after exhausting.

7. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that The precursor solution described in step 4 is specifically prepared by stirring polycarbosilane, divinylbenzene and tetrahydrofuran at a temperature of 30°C to 50°C until the polycarbosilane is dissolved; the mass ratio of the polycarbosilane to tetrahydrofuran is (1 to 1.5):1; the mass ratio of the divinylbenzene to tetrahydrofuran is (3 to 5):

1.

8. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that The heating to 300°C-320°C described in step 5 is specifically carried out according to the following steps: heating to 80°C-100°C at a heating rate of 3°C / min-5°C / min, then heating to 200°C-220°C at a heating rate of 5°C / min-10°C / min, and then heating to 300°C-320°C at a heating rate of 3°C / min-8°C / min; cooling described in step 5 is specifically carried out according to the following steps: cooling to 200°C-220°C at a cooling rate of 3°C / min-8°C / min, then cooling to 80°C-100°C at a cooling rate of 5°C / min-10°C / min, and then cooling to room temperature at a cooling rate of 3°C / min-5°C / min.

9. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that The heating to 1100℃~1300℃ in N2 atmosphere described in step 6 is specifically carried out according to the following steps: heating to 80℃~100℃ at a heating rate of 3℃ / min~8℃ / min, then heating to 700℃~800℃ at a heating rate of 5℃ / min~10℃ / min, and then heating to 1100℃~1300℃ at a heating rate of 3℃ / min~8℃ / min; cooling in N2 atmosphere described in step 6 is specifically carried out according to the following steps: cooling to 700℃~800℃ at a cooling rate of 3℃ / min~8℃ / min, then cooling to 80℃~100℃ at a cooling rate of 5℃ / min~10℃ / min, and finally cooling to room temperature with furnace water.

10. The FDM molding method according to claim 1 f / SiC ceramic composite material method, characterized in that In step 7, the C f Repeat steps 4 to 6 for the skeleton material until the weight gain is ≤ 1%.